Acoustic properties of reed panels - César Díaz; Montaña Jiménez; María A. Navacerrada; Antonio Pedrero (Materiales de Construccion, 2012)
Reed is a plant species very similar to common cane which is widespread all over the Earth. It is an ecological and sustainable material which is low-cost, aesthetically attractive, easy to obtain and install, and can be used in different construction systems.